Sebuah Perbandingan Visual Preliminer antara Ceki dan Ujang Omi: Dua Kartu Permainan Tradisional Indonesia dan Leluhur Masing-masing - Perdana, Aditya Bayu; Pollard, George (Telkom University, 2024)
Historically, three kinds of game cards are known to be played in Indonesia: remi (the standard French deck), ceki, and ujang omi. Existing literature has established that the now niche ceki and ujang omi are descendants of Chinese and Portuguese cards, based on evidence such as game mechanics and terms. Discussion of their visual characteristics, however, is still limited. Through archival comparative analysis, this paper compiles relevant samples from existing publications and digital repositories, then qualitatively describes visual similarities and dissimilarities (particularly in the suit system and court figures) in exemplary decks. The overall suit systems of ceki and ujang omi still preserve many aspects of their ancestors, but their design underwent considerable stylizations and abstractions. The visuals of ceki, which have been homogenized, are characterized by strong geometric stylization of the Chinese prototype. The underlying suit and rank are obscured, due to the stylization and Sino-centric references which are not widely understood by Indonesian players. The visuals of ujang omi are based on looser standards. Naturalistic depictions in the prototype Portuguese deck are generally simplified. Suit symbols tend to become abstract, conflating shapes. Comparison to more variations of ujang omi is needed to make a more definitive evaluation. Thus, despite their now limited usage, the design of ceki and ujang omi still shows historic cosmopolitan influence woven into the everyday life of Indonesians.